Origin of Memoir Literature in Hindi: हिन्दी बाल में संस्मरण साहित्य का उदगम - Koli, Munshi Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The development of literature of any language is like a river. Just as a small river turns into a stream in the beginning, similarly the development of any literature is narrow in the beginning and gradually takes a larger form. No starting point can be determined for the development of memoir literature in Hindi literature, but its maximum development took place during the Mughal period. Most of the features of memoir literature were incorporated in the subjective and extra-judicial biographies written by the rulers and their courtiers of the Mughal period. Abstract in Hindi Language: किसी भी भाषा के साहित्य का विकास एक सरिता के समान होता है। आरम्भ में जिस प्रकार एक लघु नहीं सुलिकाय में परिवर्तित हो जाती है उसी प्रकार किसी भी साहित्य का विकास प्रारंभ में संकुचित होता और धीरे-2 वृहद रूप धारण करता जाता है। हिन्दी साहित्य में संस्मरण साहित्य का विकास का कोई आरंभ बिन्दु निष्चित नहीं किया जा सकता परंतु इसका सर्वाधिक विकास मुगल काल में हुआ। मुगल काल के शासकों और नके दरबारियों के द्वारा जो आत्मपरक और परपरक जीवनियां लिखी उनके संस्मरण साहित्य की अधिकाधिक विशेषताएँ समाहित की गई। Keywords: साहित्य, सरिता, सुलिकाल, संस्मरण, जीवनी, समाहित, मेगस्थनीज, फाहयान, हेनसांग।